Prenatal Sonographic Features of Hypospadia: Two- and Three-Dimensional Findings - Kung-Hong Fang; Joung-Liang Wu; Ming Chen; Guang-Perng Yeh; Pan-Hsin Chou; Jui-Chang Hsu; Charles Tsung-Che Hsieh (Elsevier, 2006)
Objective: To present our experience of applying three-dimensional ultrasonography in prenatal diagnosis of hypospadia. Case Report: A 28-year-old woman, gravida 1, para 0, visited our hospital at 17 weeks' gestation. No gross anomaly was found on the scan at 21 weeks' gestation. Fetal growth was appropriate for gestational age on two-dimensional (2D) ultrasonography at 27 weeks' gestation, but an abnormally curved and shortened fetal penis was found incidentally. Three-dimensional (3D) imaging in surface-rendered mode was used to reconstruct the fetal penis. Multiplanar and surface-rendered images were obtained in the midsagittal, axial, and coronal planes to precisely delineate the ventral curvature of the penis. At 39 weeks' gestation, a term newborn was delivered by vacuum extraction. On examination, the fetus was confirmed to have hypospadia. Karyotyping revealed 46,XY. Conclusion: 2D ultrasonography could only give indirect clues of hypospadia that was later more precisely delineated by 3D ultrsonography in surface-rendered mode.